PROBLEMS OF CHILDHOOD AND EDUCATION IN CH.DICKENS’ WORKS - Aktamova Zarnigor Yahyo qizi; Xalilova Mohinurbonu Jalolovna; Khamitov Eldorbek Erkin O’g’li (Ta’lim innovatsiyasi va integratsiyasi, 2024)
ABSTRACT One of the central themes in Charles Dickens' work is the critique of society, particularly focusing on the poor education and harsh labor conditions faced by children. This article indeed provides essential information on the harsh conditions of childhood and the inadequacy of education in the writer's work, highlighting how these themes are intricately woven into the fabric of his narratives.